In Vitro Digestibility Study: Evaluating Plant Proteins Digestibility in Anabas testudineus and Channa punctata: In vitro digestibility study in A. testudineus & C. punctata - Rita Devi; Monika Basumatary; Bichitra Narzary; Heikham Dayami; Sanraja Muchahary; Bronson Kumar Khangembam (Journal of Tropical Life Science, 2022)
Protein is the most important component of any fish feed for its role in growth, especially during the larval stages, and its high cost. Fish meal continues to be a major source of protein in fish feed production. But its supply cannot keep pace with ever-expanding aquaculture production, leading to its high cost. Plants are being considered as potential replacements in the search for new alternatives to fish meals. But their application depends significantly on their digestibility in target species. The present study aims to determine the protein content of four locally available plants Moringa oleifera, Ipomoea aquatica, Lemna minor and Salvinia natans, and test their digestibility in vitro by using the pH drop method in two important food fish Anabas testudineus and Channa punctata, of Assam, India. The crude protein in all plants ranged from 19-29%, and the highest crude protein was observed in Lemna minor (29.9 Â± 2.34%). The in vitro digestibility was estimated by calculating the RPD% (relative protein digestibility) using casein as a standard reference. Digestibility of the plant proteins exhibited species-specific variations. The RPD% ranged from 50.39% to 75.39% in A. testudineus, and 41.38% to 54.02% in C. punctata compared to that of Â casein (100%). The highest RPD% was observed in I. aquatica (75.39%) for A. testudineus, and the lowest (50.39%) in L. minor whereas, in C. punctata, the highest RPD% was observed in L. minor (54.02%) and the lowest in I. aquatica (41.38%). The digestibility of all plant proteins was comparatively higher in A. testudineus than in C. punctata. Our results indicate that I. aquatica and L. minor may be a suitable replacement for animal protein in the diet of A. testudineus and C. punctata, respectively, because of their good protein content and high digestibility. Moringa may be considered for utilization in the fish feed as it recorded good protein and digestibility. This information may be useful in developing a cost-effective, plant-based protein diet for the two fish species for their mass production.